The impact of hCG trigger versus dual trigger on reproductive outcomes in elderly infertile women: a retrospective cohort study - Tingting Wang; Jinxin Ren; Zhaokang Qi; Xuanang Li; Shan Xiang; Shuai Zhao; Yi Yu; Fang Lian; Yuewen Zhao (Frontiers in Endocrinology)
PurposeThis study was designed to evaluate the effects of dual trigger (GnRH agonist and hCG) compared with hCG trigger alone on oocyte quality, embryo development, and pregnancy outcomes in elderly women (aged≥35 years) who underwent IVF treatment with an antagonist stimulation protocol, aiming to identify the more optimal triggering strategy.MethodsThis retrospective cohort study analyzed 449 elderly infertile women (≥35 years) who underwent antagonist stimulation protocols, including 236 patients in the hCG trigger group and 213 patients in the dual trigger group. The study compares the age, gravidity, parity, body mass index (BMI),anti-Müllerian hormone (AMH),gonadotropin (Gn) days, Gn dosage, trigger day luteinizing hormone (LH), trigger day estradiol (E2), trigger day progesterone (P), number of follicles ≥14mm on trigger day, number of oocytes retrieved, two pronuclei (2PN) fertilization rate, cleavage-stage embryo number, blastocyst number, embryo implantation rate (IR), clinical pregnancy rate (CPR), live birth rate (LBR), and miscarriage rate between the two groups. Multivariate logistic regression was used to analyze the influencing factors of CPR in patients.ResultsThere were no significant differences in baseline and cycle data between the two groups. In terms of oocyte and embryo outcomes, the number of oocytes retrieved (P=0.018), 2PN fertilization rate (P=0.046), and cleavage-stage embryo number (P=0.032) were significantly higher in the dual trigger group than in the hCG trigger group. There was no significant difference in the number of blastocysts obtained in the cycles of the two groups (P=0.689). In terms of pregnancy outcomes, the CPR per embryo transfer (ET) cycle (P=0.010),the CPR per frozen embryo transfer (FET) cycle (P=0.011), total embryo IR (P<0.001), total CPR (P<0.001), CPR per patient (P=0.003), total LBR (P<0.001), and LBR per patient (P=0.001) were all significantly higher in the dual trigger group than in the hCG trigger group. There was no significant difference in the miscarriage rate between the two groups (P=0.841). No cases of ovarian hyperstimulation syndrome (OHSS) occurred in either group.ConclusionFor elderly women undergoing antagonist stimulation protocols, the use of dual trigger, is more effective than hCG trigger alone in improving oocyte quality, embryo outcomes, and pregnancy outcomes.